Assuring quality in vocational education and training : the role of accrediting VET providers - (:unkn) unknown (Office for Official Publications of the European Communities, 2011)
This publication examines how accreditation systems relate to quality assurance by means of 12 in-depth case studies. Of these, four relate to economic sectors, eight to countries. The results show that accreditation systems are widely accepted by providers, and deliver vocational education and training to predefined quality standards - with or without the direct involvement of public authorities. Accreditation has a clearing effect: weak performers disappear from the market and successfully accredited providers become more visible. The use of quality labels could be more widespread. It is mostly found in the sectoral examples, especially where the value of such labels can be clearly defined. While the main function of the analysed accreditation systems is to is to assure respect of minimum standards in VET delivery, the main future challenge is to turn accreditation into a driving force for better quality. To progress this objective, study suggests a multistep approach to accreditation and concludes with recommendations for national, sectoral and European stakeholders. (Hrsg., BIBB-Doku)
Keywords: Qualitätssicherung; Berufsausbildung; Berufliche Weiterbildung; Bildungsträger; Zertifizierung; Fallstudie; Bundesrepublik Deutschland; Dänemark; England; Frankreich; Italien; Rumänien; Ungarn